Modern educational environment - N. P. Franchuk (Academy of Cognitive and Natural Sciences, 2017)
Research purpose is improvement of modern educational environment. The task of the research is to ascertain of urgent problems which require theoretical and experimental solution. A research object is the teaching process in higher education institution, the research subject is modern information-communication technologies. The result of the study is the educational process as balanced work of teachers and students during the combined organic and educationally prudent use of traditional and new facilities of teaching. Disclosed possibility of using cloud technologies in the educational process by the example of the course "Computer-oriented system of education of computer science and foreign language".